Alana in Hamyar poetry (Journal of the College of Basic Education, 2024)
The duality of the ego and the other is one of the most important topics that have secured its place in the world of thought, as it has formed the focus of study and interest of researchers and critics in order to capture its lights and provide a clear picture of this dialectic, as the research at the heart of this duality is related to the development that man has become, which sometimes leads him to Ambiguity and ambiguity, just as the philosophical background of the ego and the other, and its dress in literature and criticism, increased its complexity and study, and this duality is characterized by inseparability, as it is not possible to talk about the ego without thinking about the other, just as the existence of the ego requires the necessity of the existence of the other, and the following is an attempt to set a conceptual framework for this binary.